Biophilic smart cities: the role of nature and technology in enhancing urban resilience - Sara Tarek (SpringerOpen, 2021)
Abstract The purpose of the study is to identify the main indicators and aspects for applying biophilic and smart solutions in city planning and design to achieve urban resilience. This research investigates the main definitions, elements, and attributes for biophilic design and smart city planning that help in developing resilience strategies for healthier urban environments. This study follows a methodology that comprises two approaches; first a concise review definition and principles of urban resilience. Then investigating the notions of biophilic and smart approaches to achieve healthier urban environments. Second, an analytical approach that proposes a framework for applying biophilic and smart city indicators to achieve urban resilience. The proposed framework highlights the achieved adaptive capacities for resilient cities due to adopting biophilic and smart solutions. The research results highlight a proposed relationship between principles of urban resilience, biophilic city indicators, and smart city indicators.